Synthesis and Antibacterial Activity of Isoniazid Derivatives of Embelin† - Venkateswarlu, Somepalli; Sethu Ramu, Kavuri; V. Subbaraju, Gottumukkala (Asian Journal of Chemistry, 2010)
Condensation of embelin with isoniazid afforded N1-(5-hydroxy- 6-undecyl-p-benzoquinone-2-yl) isonicotinyl hydrazide and 7- hydroxy-3-nicotinyl-5-undecyl-4,1,2-benzoxadiazin-6H-one in 20 and 60% yield respectively. The resulting compounds showed moderate antibacterial activity.